Dataset. Error de Tipo I del estadístico F, pruebas F ajustadas de Greenhouse-Geisser y Huyhn-Feldt, y F boostrap en diseños Split-plot. - Blanca-Mena, María José; Alarcón-Postigo, Rafael; Bono Cabré, Roser; Arnau Gras, Jaume; García-Castro, F. Javier; Vallejo, Guillermo (Universidad de Málaga, 2025)
Tables that correspond to the performance of in terms of Type I error in split-plot designs under violation of normality, sphericity, and homogeneity.
Keywords: Diseño experimental; Análisis de varianza; Psicología - Investigación; Normality; Sphericity; Homogeneity; Split-plot design